Spatial analysis of sustainable development goals: A correlation between socioeconomic variables and electricity use - Marcondes dos Santos, Herivelto Tiago [UNESP]; Perrella Balestieri, José Antônio [UNESP] (Elsevier, 2018)
It is believed that the environment is largely susceptible to changes in human behavior and the constant advances in using new technologies. Different challenges with regard to housing, basic services, food, health, education, and natural resources must be overcome as it is expected an urban population growth in the upcoming decades. Thereby, a proposal has been formulated herein with the aim of understanding the correlation between a group of socioeconomic and environmental variables that tend to represent how cities of a metropolitan region in Brazil behave towards the duality of social development and electricity use. For such a purpose, a spatial econometric analysis has been conducted on sets of variables that are associated with sustainable development goals (SDGs) established to understand social vulnerabilities, economy, electricity use, health and population. The Euclidean distance has been used on standardized variables for the 39 cities in the Metropolitan Region of Paraíba Valley and North Coast as an alternative to that suggested by spatial econometrics. The region under study presents hub cities whose economies are mainly based on industry, trade and services. The results show good consistency and reveal the correlation between SDGs as regards care for vulnerable people, mainly women, children and the elderly.
Keywords: Electricity use; Social vulnerabilities; Spatial econometric analysis; Sustainable development goals